Towards Behavioral Political Economy of Institutional Change: With Field Facts from China - Yongjing Zhang; Mei Wang (Center for Economic Studies and ifo Institute (CESifo), 2014)
This study proposes an analytical framework towards behavioral political economy of institutional change. It considers institutional changes as central government's choices under uncertainty, which are largely driven by the strategic outcomes in a behavioral coordination game between local officials and private businessmen. With field facts in China, this study suggests that institutional changes begin with pro-competition policies, then a better protection of property rights, followed by a possible standstill or even worse rule of law.
Keywords: D03; D70; O43; P26; 330; behavioral economics; China; institutional change; political economy